The need for a usable assessment tool to analyse the efficacy of emergency care systems in developing countries: proposal to use the TEWS methodology. Issue 11 (20th December 2011) - Sun, Jared H; Twomey, Michele; Tran, Jeffrey; Wallis, Lee A
Abstract : Background: Ninety percent of emergency incidents occur in developing countries, and this is only expected to get worse as these nations develop. As a result, governments in developing countries are establishing emergency care systems. However, there is currently no widely-usable, objective method to monitor or research the rapid growth of emergency care in the developing world. Methods: Analysis of current quantitative methods to assess emergency care in developing countries, and the proposal of a more appropriate method. Results: Currently accepted methods to quantitatively assess the efficacy of emergency care systems cannot be performed in most developing countries due to weak record-keeping infrastructure and the inappropriateness of applying Western derived coefficients to developing country conditions. As a result, although emergency care in the developing world is rapidly growing, researchers and clinicians are unable to objectively measure its progress or determine which policies work best in their respective countries. We propose the TEWS methodology, a simple analytical tool that can be handled by low-resource, developing countries. Conclusions: By relying on the most basic universal parameters, simplest calculations and straightforward protocol, the TEWS methodology allows for widespread analysis of emergency care in the developing world. This could become essential in the establishment and growth of new emergency care systems worldwide.